Development and Deployment of Autonomous Weapon Systems: Comprehensive Analysis of International Humanitarian Law - Khalil, Ahmad (PRAWO i WIĘŹ, 2024)
This paper addresses the problem of the need to determine the legality of autonomous weapon systems (AWS) under international humanitarian law (IHL), focusing on the two targeting and weapons laws. This study emphasizes the need not to confuse these two laws in the analysis. The paper aims to clarify whether AWS could be considered illegal under IHL, taking into account the principles of distinction, proportionality, and precaution. The research methodology includes an analysis of the relevant provisions of IHL and customary humanitarian law. The research design includes an examination of the potential of AWS to cause unnecessary injury or suffering and their classification as indiscriminate weapons. The paper concludes that while AWS posses autonomous decision-making capabilities, human oversight is required to prevent excessive harm.